Peran Penyuluh Pertanian Terhadap Pengembangan Usahatani Padi - ginting, nina maksimiliana (AGRICOLA, 2020)
This study aims to look at the role of agricultural extension workers in the development of rice farming. The study was conducted in Sugihen Village, Juhar District, Karo District, North Sumatra Province. Samples were 40 members of the Sageng farmer group. The data analysis method used is a simple method of determining scores. The results and discussion show that farmer's assessment of instructors as educators is 107 and a score of 94-120, it can be concluded that the assessment of farmers to instructors as educators has a positive role. Farmer assessment of the instructor as a leader as much as 107 and a score of 94-120, it can be concluded that it can be concluded that the assessment of the farmer to the instructor has a positive role. Farmer's assessment of the counselors as advisors is 106 and a score of 94-120, it can be concluded that it can be concluded that the role of instructors as advisors has a positive role